2016
DOI: 10.1002/app.44094
|View full text |Cite
|
Sign up to set email alerts
|

Extrusion foaming behavior of a polypropylene/nanoclay microcellular foam

Abstract: With maleic anhydride grafted polypropylene (PP-g-MAH) as a compatibilizer, composites of block-copolymerized polypropylene (B-PP)/nanoclay were prepared. The effects of the PP-g-MAH and nanoclay content on the crystallization and rheological properties of B-PP were investigated. The microcellular foaming behavior of the B-PP/nanoclay composite material was studied with a single-screw extruder foaming system with supercritical (SC) carbon dioxide (CO 2 ) as the foaming agent. The experimental results show that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 14 publications
0
14
0
Order By: Relevance
“…In Figure (a), the η * curve of torqued PBAT sample displayed a Newtonian plateau, but others did not. This transition from a Newtonian plateau to the shear thinning regime indicated the presence of microstructure (branching and/or crosslinking structure) with a long relaxation time . The η * of CE‐PBAT samples increased with the increment of CE content, which should be resulted from the increase of molecular weight and the formation of branching and/or crosslinking structures .…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…In Figure (a), the η * curve of torqued PBAT sample displayed a Newtonian plateau, but others did not. This transition from a Newtonian plateau to the shear thinning regime indicated the presence of microstructure (branching and/or crosslinking structure) with a long relaxation time . The η * of CE‐PBAT samples increased with the increment of CE content, which should be resulted from the increase of molecular weight and the formation of branching and/or crosslinking structures .…”
Section: Resultsmentioning
confidence: 94%
“…It possesses moderate crystallinity, good processability, high toughness, and well biocompatibility . Supercritical carbon dioxide (SCCO 2 ) was often used as an environment friendly physical blowing agent to prepare the microcellular polymer foaming materials due to its nontoxic, nonflammability, low global warming potential, and ozone depletion potential, as well as safe in performance …”
Section: Introductionmentioning
confidence: 99%
“…The cell structure was greatly improved, and the cells were more uniform as the absorbed dose increased from 0 to 30 kGy. The cells of the foamed PP materials became more uniform, and more closed cells were present in the foamed PP compared to the cell structure of the foamed blends of PP/nanoclay and PP/nanocrystalline cellulose by supercritical carbon dioxide-foamed PP [21,22]. Moreover, the cells have a relatively stable diameter for doses from 10 kGy to 40 kGy, owing to a larger cross-linked region and higher melt strength of PP, which is beneficial for bearing the pressure of CO 2 .…”
Section: Morphology Of Cross-linked Pp Foamsmentioning
confidence: 96%
“…However, compared to polyethylene, isotactic polypropylene more easily undergoes degradation upon irradiation, resulting in a poorer resistance to weathering [18,19]. Many studies have been performed on the foaming of PP by scCO2 [20][21][22]. The melt strength and mechanical and heat-resistant properties of polypropylene have been shown to be significantly improved by irradiation in the presence of a cross-linking agent [23].…”
Section: Gel Content and Melt Flow Index Analysesmentioning
confidence: 99%
“…Addition of organoclay containing 5 wt% of polybutadiene powder improved the mechanical properties of the foamed PP relative to adding either filler by itself. Wang et al [21] used maleic anhydride-grafted polypropylene (PP-g-MAH) as a compatibilizer to study the effects of PP-g-MAH and nano-clay content on the crystallization and rheological properties of block-copolymerized polypropylene (B-PP). They found that adding nano-clay and PP-g-MAH decreased the melt strength and complex viscosity of B-PP.…”
Section: Introductionmentioning
confidence: 99%